2006
DOI: 10.1183/09031936.06.00078605
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone can stimulate G1-S phase transition in human airway fibroblasts in asthma

Abstract: Corticosteroids are the first line of therapy for asthma. Whether they alter the progression of airway remodelling in asthma is, as yet, unknown.To determine whether corticosteroids could alter the fibroblast cell cycle the current authors studied the effect of dexamethasone on cultured airway fibroblasts obtained from nine mild-tomoderate, steroid-naïve asthmatics (forced expiratory volume in one second 78¡4% predicted), and seven normal controls. Fibroblasts were cultured from endobronchial biopsies obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 31 publications
4
13
1
1
Order By: Relevance
“…6,24,25 On the other hand, some in vitro studies suggested that steroids could increase extracellular matrix deposition. 26 Nonetheless, whereas the patients with the most severe asthma had the highest RBM thicknesses, in the current study we noted, like Minshall et al 27 in a previous study, a negative correlation between RBM thickness and FEV 1 when considering the 2 asthma groups. In a variable and heterogeneous condition such as severe asthma, a single parameter such as FEV 1 did not account for the complexity of the disease.…”
Section: Discussionsupporting
confidence: 45%
“…6,24,25 On the other hand, some in vitro studies suggested that steroids could increase extracellular matrix deposition. 26 Nonetheless, whereas the patients with the most severe asthma had the highest RBM thicknesses, in the current study we noted, like Minshall et al 27 in a previous study, a negative correlation between RBM thickness and FEV 1 when considering the 2 asthma groups. In a variable and heterogeneous condition such as severe asthma, a single parameter such as FEV 1 did not account for the complexity of the disease.…”
Section: Discussionsupporting
confidence: 45%
“…69,70 However, studies using fibroblasts from patients with asthma show that dexamethasone can increase fibroblast proliferation and stimulate G1-S phase transition. 71,72 This is an important observation, suggesting that corticosteroids may also promote elements of airway remodeling in asthma. FP displays anti-inflammatory effects on human lung fibroblasts during their myofibroblastic differentiation.…”
Section: Lamina Propriamentioning
confidence: 91%
“…Sequential 2-mm sections were cut from glycomethacrylate-embedded bronchial biopsies and stained using mAbs against a-smooth muscle actin (a-SMA; Dako, Ely, U.K.), mast cell tryptase (Dako), the fibroblast marker Thy-1 (Ab1) (Calbiochem, San Diego, CA) (20) (7,13,15). The whole biopsy was assessed, and a minimum area of 0.1 mm 2 was considered assessable, as described previously (7).…”
Section: Immunohistochemistrymentioning
confidence: 99%